Microstructure and anodic dissolution mechanism of brazed WC–Ni composite coatings. (May 2014) - Gao, L. X.; Zhou, T.; Zhang, D. Q.; Lee, K. Y.
<x content-type="archive" xml:space="preserve">Abstract</x> WC–Ni composite coatings were prepared on the mild steel substrates by high temperature sinter brazing. Potentiodynamic polarisation was performed on the coated sample immersed in 3%NaCl solution. Two limited current plateaus appear in the anodic polarisation curve. The first limited current plateau is attributed to the formation of Ni and Cr oxide, while the second corresponding to W oxide. The surface morphology observation and composition analysis after anodic polarisation were investigated by the scanning electron microscopy (SEM) with energy dispersive X-ray (EDX) spectroscopy. The elemental concentrations in the immersion solution were studied with inductively coupled plasma (ICP) spectroscopy. It shows that the selective dissolution of Ni base binder alloy as well as the electrochemical dissolution of WC exists during the anodic polarisation process.